Improving Education Quality in South Africa - Murtin, Fabrice (OECD Economics Department Working Papers, 2013)
South Africa has achieved remarkable progress in educational attainment relative to other emerging countries, but the quality of basic education for a large fraction of the Black African population is still very low. This study identifies several hurdles to the upgrading of basic education quality, such as the lack of investment in school infrastructure and learning materials in disadvantaged areas, uneven administrative capacity at the local level, low teacher quality and poor teaching of English among Black Africans. Bold action is recommended to empower schools with more physical resources, more competent school leadership and an accountable teacher workforce. Skill mismatches of supply and demand on the labour market may be further addressed by vocational education reforms and an alleviation of credit constraints at the tertiary level